Strengthening the CHIIR community: Bridging interactive IR and HCI at CHI 2026 - Liu, Haiming; Capra, Rob; Thomas, Paul; Kamps, Jaap; Bogers, Toine; Harvey, Morgan A; Jones, Rosie; Liu, Chang; Kruschwitz, Udo; Makri, Stephann; Sitbon, Laurianne; Roegiest, Adam; et al. (Proceedings of the Extended Abstracts of the CHI Conference on Human Factors in Computing Systems, 2026)
This meet-up will bring together members of the ACM SIGIR Information Interaction and Retrieval (CHIIR) community and the broader CHI audience to strengthen cross-community dialogue on interactive information retrieval (IIR), search interfaces, and human-centered evaluation methods. Through structured activities, networking opportunities, and collaborative brainstorming, the session aims to identify common challenges, inspire collaborations, and chart a forward-looking research agenda that connects CHI and CHIIR communities.